Information Technology is Important To Solve Crimes - Dayaani a/p Nathan (IC-ITECHS, 2020)
The twenty-first century is known as the age of Information Technology. The term ‘Information Technology’ is given to all advancements of technology in the world. Modern progress in technology, learning, and information has led to immense possibilities. Lots of benefits from these new inventions but have we really taken the negative part of the technology seriously? Technology has been taken advantage by certain people and it has caused so many serious problems and deaths around the world. People carelessly put out their personal information to the public which causes them to fall into the dangerous trap of technology. We should take the responsibility to learn how to keep ourselves safe from falling into this negative trap which is also known as Cybercrime. As a technology user, we must learn how to keep ourselves and our personal data safe from hackers. How do we do that? We should download antivirus protection to protect our computer from malware, we should update the antivirus protection daily, we should use effective password for all the social medias we use, we shouldn’t click on unknown software, we shouldn’t be fooled by catchy title or phrases that pops-up on certain websites, we should guard our own personal data by making our account private, we should only let in people we trust and know, and we should repost account that posts inappropriate contents. In conclusion, this study discussed on how to use technology to avoid Cybercrime from happening. Through these steps we can surely safe our and others’ life.